Asymmetric epoxidation of enones: effect of surfactants, radical scavengers and morphology of catalysts on reaction rates, chemical yields and enantioselectivities in phase-transfer catalysis. Issue 18 (4th August 2022) - Lee, Geumwoo; Lee, Jeong-Hee; Lee, Jaeyong; Ha, Min Woo; Kim, Mi-hyun; Hong, Suckchang; Park, Hyeung-geun
Abstract : Highly enantioselective epoxidation of enones has been accomplished with asymmetric phase-transfer catalysis using Cinchona alkaloid-derived meta -dimer catalysts. Abstract : A highly enantioselective epoxidation of enones has been accomplished with asymmetric phase-transfer catalysis (PTC) using Cinchona alkaloid-derived meta -dimer catalysts. An intensive study of the structure–reactivity relationships among catalysts and oxidants in terms of chemical yields and enantioselectivities was used to prepare optically active epoxides from enones with yields up to 99% and 99% ee at room temperature. Additionally, the first systematic investigation of the influence of surfactants on epoxidation by PTC was performed, and this resulted in surfactants that played important roles in improving reaction rates and enantioselectivities in asymmetric phase-transfer catalysis by increasing the surface between organic–aqueous phases by forming micellar emulsions when pro-nucleophiles existed predominantly in the water phase. Furthermore, radical scavengers and the morphologies of quaternary ammonium catalysts used in PTC were shown to be important for ensuring reproducible chemical yields and enantioselectivities in oxidative epoxidations by PTC. The convenient synthesis of the best catalyst 13 and the very practical PTC conditions make this epoxidation method suitable for application in industrial epoxidation processes at room temperature.